Pengaruh Fasilitas dan Lokasi Terhadap Kepuasan Pengunjung Event Thaipusam Street Festival di Medan - Rinaldi Upar Ritonga; Nursiah Fitri (JURNAL RISET MANAJEMEN (JURMA), 2024)
An event is an agenda for certain activities or festivals that displays and celebrates important things that are held at a certain time with the aim of communicating messages to visitors. In every event organization, the thing that must always be prioritized is the satisfaction of event visitors. Facilities are everything provided by the company to provide convenience for customers with the aim of providing high satisfaction and being a benchmark for visitor satisfaction from all forms of services provided. Location is a company decision to determine a place of business to carry out business activities or operational activities, and to distribute goods or services that are part of its business activities to consumers. The purpose of this study was to find out whether there is an influence of facilities and location on visitor satisfaction at the Thaipusam Street festival event in Medan. This research is a type of associative research using quantitative data with a population of 5,000 people and a sample of 98 people. The data analysis technique used in this study is multiple linear regression with partial data hypothesis testing, simultaneous testing and the coefficient of determination. Facilities and location have a positive and partial effect on Visitor Satisfaction of the Thaipusam Street Festival Event in Medan. From the results of the simultaneous research it was concluded that the facilities and location simultaneously affected the visitor satisfaction of the Thaipusam Street Festival Event in Medan. The magnitude of the influence is known from multiple linear regression analysis with the result of a coefficient of determination that is equal to 11,6% indicating that the relationship between the independent variables consisting of facilities and location does not have a strong enough effect on visitor satisfaction while the remaining 88,4% is influenced by other variables not examined in this study.